SLIT2 Overexpression in Periodontitis Intensifies Inflammation and Alveolar Bone Loss, Possibly via the Activation of MAPK Pathway - Wang, Liping; Zheng, Jing; Pathak, Janak L.; Chen, Yunxin; Liang, Dongliang; Yang, Luxi; Sun, Haobo; Zhong, Mei; Wu, Lihong; Li, Li; Deng, Shuhua; Zheng, Lingyun; et al. (Frontiers in Cell and Developmental Biology, 2020)
SLIT2, a member of neuronal guidance cues, has been reported to regulate inflammation and cancer progression. Periodontitis is an oral inflammatory disease that degenerates periodontal tissue, alveolar bone and tooth. This study aims to explore the expression pattern of SLIT2 in periodontitis and its role in disease progression and bone loss. Gingival tissue of 20 periodontitis patients and 20 healthy-controls was obtained. Ligature-induced periodontitis (LIP) mice-model was developed in Slit2-Tg and wildtype-mice. The effect of SLIT2 on inflammation, immune cell infiltration, M1 macrophage polarization, and alveolar bone loss in periodontitis was analyzed extensively. In periodontitis-affected gingival-tissue, SLIT2 expression was 4.4-fold higher compared to healthy-volunteers. LIP enhanced SLIT2 expression in mice periodontitis-affected periodontal tissue (PAPT) and blood circulation of wildtype-mice by 4.6-, and 5.0-fold, respectively. In Slit2-Tg-mice PAPT, SLIT2 expression was 1.8-fold higher compared to wildtype-mice. Micro-CT and histomorphometric analysis revealed a 1.3-fold higher cement-enamel-junction to the alveolar-bone-crest (CEJ-ABC) distance and alveolar bone loss in LIP Slit2-Tg-mice compare to LIP wildtype-mice. Results from RNA-sequencing, RT-qPCR, and ELISA showed a higher expression of Cxcr2, Il-18, TNFα, IL-6, and IL-1β in Slit2-Tg-mice PAPT compared to wildtype-mice. Slit2-Tg-mice PAPT showed a higher number of osteoclasts, M1 macrophages, and the upregulation of Robo1 expression. Slit2-Tg-mice PAPT showed upregulation of M1 macrophage marker CD16/32 and osteoclastogenic markers Acp5, Ctsk, and Nfatc1, but osteogenic markers (Alp, Bglap) remained unchanged. Immunohistochemistry unveils the higher vasculature and infiltration of leucocytes and macrophages in Slit2-Tg-mice PAPT. RNA-sequencing, GO-pathway enrichment analysis, and western blot analysis revealed the activation of the MAPK signaling pathway in Slit2-Tg mice PAPT. In conclusion, SLIT2 overexpression in periodontitis intensifies inflammation, immune cells infiltration, M1 macrophage polarization, osteoclastogenesis, and alveolar bone loss, possibly via activation of MAPK signaling, suggesting the role of SLIT2 on exacerbation of periodontitis and alveolar bone loss.